An assessment of the C-reactive protein, erythrocyte sedimentation rate and white blood cell count, values during the post-operative period of infected tibial nonunions treated with antibiotic- loaded PMMA-coated nails - Dırvar, Ferdi; Özcafer, Raşit; Beng, Kubilay (International Journal of Research in Orthopaedics, 2021)
In this study, our aim was to assess the changes in the serum C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), and white blood cell count (WBC) values during the follow-up period of infected tibial pseudoarthrosis treated using antibiotic-loaded nails. Three patients with infected femoral nonunions and 11 patients with infected tibial nonunions were included in the study. All patients were treated with intramedullary nails coated with antibiotic-loaded PMMA after local extensive debridement. Postoperatively, parenteral antibiotic therapy was administered. The CRP, ESR and WBC values were noted preoperatively and on the first day, and then on the second, sixth, and 12th weeks postoperatively. The changes in these values over time were analyzed comparatively. The preoperative CRP level was found to be significantly lower than the early postoperative period (1st day), while no significant differences were detected during the follow-up period. The CRP level constantly decreased between the first postoperative control (1st day) and the final follow-up time (12th week). The postoperative ESR showed a significant difference when compared to the preoperative value, and also showed a decreasing trend in the postoperative period, having its highest value on the first day. The WBC did not exhibit a significant difference when comparing the preoperative and postoperative values. C-reactive protein level and ESR can be used to monitor the adequacy of the treatment after antibiotic-loaded nail application, whereas WBC may be insufficient in the diagnosis and follow-up of osteomyelitis treated with antibiotic-loaded nails.